A novel metalporphyrin-based microporous organic polymer with high CO2 uptake and efficient chemical conversion of CO2 under ambient conditions. Issue 4 (22nd December 2016) - Wang, Shaolei; Song, Kunpeng; Zhang, Chengxin; Shu, Yu; Li, Tao; Tan, Bien
Abstract : A novel metalporphyrin-based microporous organic polymer (HUST-1-Co), which exhibits a high CO2 uptake and efficient chemical conversion of CO2 under ambient conditions, is reported. Abstract : A novel metalporphyrin-based microporous organic polymer (HUST-1-Co), which possesses a high surface area of 1360 m 2 g −1 and a high CO2 uptake of 21.39 wt% (1 bar and 273 K) for CO2 capture and storage (CCS) and the efficient chemical conversion of CO2 under ambient conditions, is reported. This polymer incorporated both ultra-micropores and catalytic sites, and was synthesized by a novel solvent knitting hypercrosslinked polymers method, using 5, 10, 15, 20-tetraphenylporphyrin (TPP) as the building block. The N2 sorption isotherms of the polymers show that HUST-1-Co possesses abundant ultra-micropores (centered at 0.68 nm), and a continuous mesoporous and macroporous structure, which not only enhances the interaction between the pore walls and CO2, but is also favourable for the catalysis process. The synergy of the ultra-micropores, abundant nitrogen atoms and Co 2+ ions makes HUST-1-Co one of the highest CO2 uptake MOP materials reported so far and further endows it with efficient catalytic performance. HUST-1-Co is one of the most efficient catalysts for the coupling of CO2 with substituted epoxides with various functional groups at room temperature and atmospheric pressure, with an excellent recycling performance (more than 15 times). Moreover, the role of the mesoporous and macroporous structure of HUST-1-Co gives it a unique catalytic performance for different molecular sizes of epoxide substrates with excellent yields (>93%).